CLINICAL STUDIES ON THE EFFICIENCY OF A PROFESSIONAL PRODUCT APPLIED TO TEETH WITH DENTIN HYPERSENSITIVITY - Cristina-Angela Ghiorghe; Claudiu Topoliceanu; Gianina Iovan; Simona Stoleriu; Galina Pancu; Irina Nica; Lucian Savencu; Sorin Andrian (Romanian Dental Association for Education, 2019)
The aim of this study was to assess, by using VAS indices and SCHIFF scale, the effectiveness of a desensitising product with role in the blocking of the dentinal tubules, at 24 hours and 1 week after its application. Material and methods. The clinical study was performed on 37 teeth (7 incisive; 9 canines; 17 premolars and 4 molars), divided in two groups: Group 1 (n = 18) -teeth treated with desensitiser agent Voco Profluorid® Varnish; Group 2 (n=19) -placebo (distilled water). Results. VAS indices at baseline were 5.14 (at stimulation with air spray). 24 hours after desensitising session the mean value of VAS indices decreased, in group 1, from 6.07 to 1.00. 1 week after desensitising session the mean value of VAS indices was 1.03. VAS indices for placebo group remained 3.05. Schiff indices at baseline had 1.78 mean values for the teeth taken in study. Schiff indices for group 1 decreased from 2.38 to 0.357 after 24 hours, and increased to 0.864 after 1 week. Placebo group had the same Schiff value (0.86) during the study period. Conclusions. Voco Profluorid® Varnish was effective in the treatment of the dental cervical hypersensitivity with one single session, and the desensitising effect was maintained after 1 week. The use of this product in multiple treatment sessions could determine the complete closure of the dentinal tubules.